A Descriptive Study on the Implementation of the Electronic-Based Government System (SPBE) (Future Science, 2025)
Digital transformation in Indonesian governance is manifested through the Electronic-Based Government System (SPBE), which aims to enhance bureaucratic effectiveness, transparency, and the quality of public services. Although regulated at the national level, the implementation of SPBE at the regional level still faces various obstacles related to limited human resources, technological infrastructure, and inter-agency coordination. This study seeks to describe the process of implementing SPBE policy in local governments, identify its supporting and inhibiting factors, and analyze its impact on bureaucratic effectiveness and public service delivery. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis, and analyzed using thematic techniques to identify patterns and key themes. The findings indicate that SPBE implementation at the regional level is characterized by the adoption of local regulations, the provision of electronic service applications, and efforts to improve bureaucratic accountability. However, barriers such as limited staff capacity, weak coordination among local government agencies, and unequal infrastructure access continue to reduce implementation effectiveness. This research contributes to broadening the understanding of the relationship between public policy implementation theory and good governance principles in the context of government digitalization, while also offering practical implications regarding the importance of strengthening human resource capacity, integrating information systems, and expanding equitable digital infrastructure as prerequisites for successful SPBE at the regional level.